Lyapunov-Type Inequalities for a Conformable Fractional Boundary Value Problem of Order 3<α≤4 - Imed Bachar; Hassan Eltayeb (Journal of Function Spaces)
We establish new Lyapunov-type inequalities for the following conformable fractional boundary value problem (BVP): Tαaut+q(t)u(t)=0,  a<t<b,  u(a)=u′(a)=u′′(a)=u′′(b)=0, where Tαa is the conformable fractional derivative of order α∈(3,4] and q is a real-valued continuous function. Some applications to the corresponding eigenvalue problem are discussed.